Exploring the Effectiveness of E-Learning in Boosting Motivation for Islamic Education Teaching Methods Among Future Educators - Supardi Ritonga; Decky Saputra; Koiy Sahabudin Harahap; Amri Amri (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study investigates the influence of e-learning strategies on the learning motivation of prospective teachers in the Islamic Religious Education (PAI) Study Program at STAIN Bengkalis. The integration of digital tools is becoming increasingly relevant in enhancing student engagement and academic performance. A quantitative research design was employed using regression analysis. Data were gathered from 90 fifth-semester students through closed-ended questionnaires, focusing on their motivation levels in relation to the use of technology-based learning media, including e-books, educational videos, and online discussions. The findings indicate that e-learning strategies have a significant positive impact on student motivation, accounting for 45% of the variance in learning motivation. However, 55% of the variation is attributed to other factors, such as personal interest in the subject matter and self-efficacy. These results suggest that while e-learning tools are effective in boosting motivation, they are not the sole contributors. Internal factors and individual learner differences also play a crucial role and must be addressed to fully optimize learning outcomes. E-learning strategies significantly enhance motivation among prospective PAI teachers. However, a more comprehensive approach—considering both internal and external factors—is necessary for achieving sustained academic motivation. Future research should examine additional variables, such as time management and social interaction, to refine e-learning practices in Islamic education.